Caregiver-Reported Changes in the Socioemotional Wellbeing and Daily Habits of Children With Special Educational Needs During the First COVID-19 National Lockdown in the United Kingdom - Morgül, Evren; Kallitsoglou, Angeliki; Essau, Cecilia A.; Castro-Kemp, Susana (Frontiers in Education, 2022)
The implementation of social distancing measures (e.g., school closures) by governments worldwide to prevent the spread of COVID-19 has affected millions of children and their families. However, the consequences of such measures on the wellbeing of children with special educational needs (SEN) and their caregivers are not fully understood. The present study examined the socioemotional wellbeing and daily habits of children between 5 to 12 years old with SEN during the first national COVID-19 lockdown in the UK. Participants were 995 caregivers between 18 to 61 years old living in the UK who completed a 20 -min electronic survey on child and family wellbeing distributed via social networks between July and August 2020. The findings showed that children with SEN were more likely to experience more emotional and behavioural difficulties during the lockdown than children without SEN. Children with SEN but without mental health difficulties did not have more behaviour difficulties during the lockdown than children without SEN. There was a significant increase in screen time and decrease in sleep time for children with and without SEN during the lockdown, but children with SEN were using screens more often than children without SEN both before and during the lockdown. Finally, caregivers with children with SEN reported more difficulty with the confinement than caregivers with children without SEN, but caregiver and child poor mental health were likely to explain the difference. The findings show that the wellbeing of children with SEN were more likely to be negatively affected by the lockdown than the wellbeing of children without SEN. Caregiver and child mental health were likely to explain the differences.